Nicola Laneri (ed.), Performing Death. Social Analyses of Funerary Traditions in the Ancient Near East and Mediterranean. Oriental Institute Seminars, Number 3. Chicago, The Oriental Institute of the University of Chicago, 2007, pp. xviii + 318, con mapas e imágenes en blanco y negro. U$S 24, 95.- ISBN 1-885923-50-3. En Internet: <http://oi.uchicago.edu/pdf/ois3.pdf> - Busso, María (2007)
Fil: Busso, María. Pontificia Universidad Católica Argentina; Argentina